2020
DOI: 10.21203/rs.2.19713/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polychlorinated Biphenyls in the Drinking Water Source of the Yangtze River: Characteristics and Risk Assessment

Abstract: Background As the longest river in Asia, the Yangtze River flows through the most industrialized cities in China and provides critical ecological services for agriculture, industry, and transportation.Polychlorinated biphenyls (PCBs) have been banned for many years, but trace amounts of PCBs still exist as persistent organic pollutant in drinking water and are an ecotoxicological problem. In this work, we collected water, sediment, and suspended particulate matter (SPM) samples along the Yangtze River, to stud… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Many studies have shown that secondary effluent from WWTPs can often meet most of these criteria, and effluent from effective tertiary or advanced treatment processes can basically meet the requirements very well (Jin et al, 2013;Sun et al, 2016). However, more and more studies indicated that many emerging contaminants in wastewater and rivers may pose risks to human and aquatic ecology including pesticides (Wang et al, 2017a;Zheng et al, 2016), PCBs (Cui et al, 2020), pharmaceuticals and personal care products (PPCPs) (Ben et al, 2018;Wang et al, 2018), endocrine disrupting chemicals (EDCs) (Tan et al, 2018), disinfection by-products (DBPs) (Li et al, 2019;Wang et al, 2017b) and pathogenic contaminants (Vadde et al, 2019). These studies generally focused on the occurrence, fate, transport and toxicity of one or several types of emerging contaminants in one site such as surface water, drinking water and WWTPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that secondary effluent from WWTPs can often meet most of these criteria, and effluent from effective tertiary or advanced treatment processes can basically meet the requirements very well (Jin et al, 2013;Sun et al, 2016). However, more and more studies indicated that many emerging contaminants in wastewater and rivers may pose risks to human and aquatic ecology including pesticides (Wang et al, 2017a;Zheng et al, 2016), PCBs (Cui et al, 2020), pharmaceuticals and personal care products (PPCPs) (Ben et al, 2018;Wang et al, 2018), endocrine disrupting chemicals (EDCs) (Tan et al, 2018), disinfection by-products (DBPs) (Li et al, 2019;Wang et al, 2017b) and pathogenic contaminants (Vadde et al, 2019). These studies generally focused on the occurrence, fate, transport and toxicity of one or several types of emerging contaminants in one site such as surface water, drinking water and WWTPs.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing detection in water systems and studies on their toxicity have raised public and researchers' concern for safety of emerging contaminants in water systems. Although several recent studies (Cui et al, 2020;Ghernaout, 2018;Wang et al, 2017b) assessed the risks posed by some emerging contaminants, they are mainly focused on portable reuse or drinking water sources and associated environmental risks. By far, studies on systematic assessments of risks to human health and aquatic ecology brought by their toxicity in ecological water reuse systems, were urgently needed.…”
Section: Introductionmentioning
confidence: 99%